Evaluating Simulated Augmented Reality Interfaces in a VR Role-Playing Simulator for Police De-Escalation Training - Grandi, Jeronimo; Costa, Dalton B.; Kopper, Regis (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
This study evaluates future Augmented Reality (AR) interfaces for police de-escalation training by simulating them within a Virtual Reality (VR) role-playing platform, RESPOND. The platform uses live actors to embody avatars, creating realistic and unscripted traffic stop scenarios. We conducted a between-subjects study with 18 police officers to compare simulated AR interfaces against current procedures, measuring performance, workload, and user acceptance. Our results show that the simulated AR-enhanced procedures performed on par with traditional methods, with no significant differences in task time, interaction outcomes, or cognitive load. Despite maintaining operational performance, officers strongly preferred traditional methods (NPS = -77.78), though individual AR safety features received high ratings, revealing a critical performance-acceptance paradox. This finding of non-inferiority with resistance is critical, as it demonstrates how VR-based evaluation can uncover adoption barriers before hardware investment. These results validate the feasibility of using VR simulation to preview AR concepts for complex police work and provide a foundation for designing future systems that can enhance officer safety and effectiveness.